UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK TERHADAP MATERI SIFAT BENDA PELAJARAN IPA MELALUI METODE DISCOVERY LEARNING - Husnul Khotimah (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
The purpose of this study was to observe efforts to improve science learning material properties of objects in class IV through the discovery learning method. This research was conducted at MI Miftahul Falah Mandala in the second semester of the 2021 academic year. The reasons the researchers were interested in conducting research on leaf shape and function using the discovery learning method for fourth grade students at MI Miftahul Falah Mandala were: 1) the researcher was the child of the class teacher. IV Miftahul Mandala MI School, making it easier for researchers to conduct research at the school. 2) the material on leaf shape and function is in accordance with the competencies being taught and the leaf shape and function are in accordance with the competencies being taught and 3) efforts to improve student learning outcomes are needed through learning methods, one of which is the discovery learning method. In general, the purpose of this study is "To find out the improvement of student learning outcomes in the form of leaves and their functions with the discovery learning method at MI Miftahul Mandala. The method used in this research is descriptive with the form of research used in this study is classroom action research (CAR) which is also called Class Room Action Research (CAR).